Thermal Performance Monitoring and Optimization in Nuclear Power Plants - IAEA (International Atomic Energy Agency, 2021)
Rising operating costs and increased competition have focused attention on the need to improve thermal performance in nuclear power plants (NPPs), to ensure efficient electricity generation. Efforts to improve thermal performance require a broad understanding of NPP design, operation, maintenance, ambient conditions, and thermal sciences. This publication provides various methodologies for tracking and trending NPP thermal performance. It describes the essenti.